IMAGING OF PANCREATIC NEUROENDOCRINE TUMORS: recent advances, current status and controversies - Lee, Lingaku (Expert Rev Anticancer Ther, 2018)
INTRODUCTION: To review recent the advances, current status and controversies in of imaging of pancreatic neuroendocrine tumors(panNETs). AREAS COVERED: Recently there have been a number of advances in imaging of panNETs, as well as other NETs, which have had a profound effect on the management and treatment of these patients, but in some cases also associated with controversies. These advances include result of numerous studies attempting to better define the roles of both cross-sectional imaging, endoscopic ultrasound(EUS) with or without fine needle aspiration(EUS-FNA) and molecular imaging in both sporadic and inherited panNET syndromes; the increased attempt to develop imaging parameters that correlate with tumor classification or have prognostic value; the rapidly increasing use of molecular imaging in these tumors and the attempt to develop imaging parameters that correlate with treatment/outcome results. Each pf these areas and the associated controversies are reviewed. EXPERT OPINION/COMMENTARY: There have been numerous advances in all aspects of the imaging of panNETs, as well as other NETs, the last few years. The advances are leading to expanded roles of imaging in the management of these patients and the results in panNETs/GI-NETs with these newer aiming approaches, are already being used in more common tumors.